Tindak Pidana Money Politics Ditinjau dari Hukum Pidana Islam - Hanafi, Hanafi; Sitepu, Rajin (Legal Standing : Jurnal Ilmu Hukum, 2025)
Politics and Islam are two concepts that cannot be separated, as Islam provides guidance for all aspects of life, including political and state affairs. In Indonesia, the practice of "Money Politics" or commonly referred to as "serangan fajar" has become a widespread phenomenon in various general elections. This phenomenon involves the strategy of giving money or basic necessities by the campaign teams of candidates to the public in exchange for their votes. This practice raises various issues from moral, legal, and justice perspectives. Therefore, this study aims to analyze Money politics from the perspective of Indonesian law using a critical theory approach, as well as from the perspective of Islamic law through a normative religious theory approach. This research employs a normative juridical method, examining relevant regulations and sources of Islamic law to provide an understanding of the impact of Money politics on the legal system and political ethics. The findings indicate that Money PoliticsÂ  contradicts the principles of justice and integrity, both in Indonesian positive law and Islamic teachings. In conclusion, despite the persistence of this practice, there is a need for strengthening moral and legal values to create a cleaner and fairer political system.